The Impact of Risk Management, Business Creativity, and Business Collaboration on Business Growth Through Financial Management Quality: a Study on MSMEs - Sely Megawati Wahyudi; Putri Renalita Sutra Tanjung; Wieta Chairunesia; Riaty Handayani; Diah Iskandar (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
MSMEs play a vital role in driving urban economic growth but continue to face challenges in managing risks, fostering innovation, and building effective collaboration. In a competitive environment such as DKI Jakarta, sound financial management and the ability to convert internal capabilities into measurable performance are essential. This study analyzes the influence of risk management, business creativity, and business collaboration on MSME growth with financial management quality as a mediating variable. Using a quantitative approach and SEM-PLS analysis on 100 purposively selected MSME respondents, the findings indicate that risk management and business creativity significantly enhance growth, whereas collaboration does not. Financial management quality also indicates a strong direct and mediating effect between risk management and creativity on business growth. The study reinforces the Resource-Based View and Enterprise Risk Management Theory, emphasizing that robust financial governance strengthens innovation-based performance. Future research should expand regional coverage and explore mediators such as digital literacy or market orientation.